Exploring How Cognitive Skills, Experience, and Motivation Drive Resilience in Community Health Volunteers Implementing Post-Pandemic Posyandu in Rural Indonesia - Nila Widya Keswara; Rosyidah Alfitri; Rani Safitri (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Posyandu is a community-based health program managed by and for the community, aiming to strengthen local health systems and facilitate access to essential health services. The temporary disruption of Posyandu services during the COVID-19 pandemic has had adverse effects on vulnerable populations such as pregnant women and toddlers, highlighting the importance of resilient volunteer performance post-pandemic. This study aims to examine the correlation between post-pandemic competence and the implementation of the five main activities by Posyandu volunteers in Malang, Indonesia. Utilizing a quantitative correlational research design, the study involved a total sample of 123 Posyandu volunteers from two villages in Malang. Data collection was conducted over July to August 2023. The findings indicate a statistically significant but weak positive correlation between volunteer knowledge and motivation, with a p-value of 0.007 and a correlation coefficient of 0.242. This suggests that while increased knowledge is associated with higher motivation levels, the strength of this relationship is limited. Further analysis assessed the relationship between length of service and volunteer motivation, revealing no significant correlation (p = 0.675, r = -0.038). These results imply that the duration of volunteer service does not influence motivational levels among Posyandu volunteers. Given these findings, enhancing volunteers’ knowledge through regular training and refresher programs is essential to maintain motivation and improve service delivery. The study recommends continuous capacity-building efforts to empower Posyandu volunteers, thereby ensuring effective implementation of health activities post-pandemic. Future research should investigate additional factors that may affect volunteer motivation, such as social support, recognition, and workload. Understanding these dimensions can further strengthen Posyandu programs and support the vulnerable community members they serve.